Equinodermos (Echinodermata) de las aguas mexicanas del Golfo de México - Durán-González, Alicia (2005)
Echinoderms (Echinodermata) from the Mexican waters of the Gulf of Mexico. We present a systematic list of the echinoderms from Gulf of Mexico’s Mexican waters based on specimens of the Colección Nacional de Equinodermos, Instituto de Ciencias del Mar y Limnología, Universidad Nacional Autónoma de México and the National Museum of Natural History, Smithsonian Institution, Washington, D.C. This list reveals an important echinoderm biodiversity present in the Gulf of Mexico, where five of the six echinoderm classes are represented. A total of 209 echinoderm species is recorded, distributed in 129 genera, 63 families and 25 orders. 31 new records for the Gulf of Mexico are presented: Asteroidea (16), Ophiuroidea (nine), Echinoidea (one) and Holothuroidea (five). Rev. Biol. Trop. 53(Suppl. 3): 53-68. Epub 2006 Jan 30.